Editorial: Four tales of sci-fi and information law - Natali Helberger; Joost Poort; Mykola Makhortykh (Internet Policy Review, 2020)
Feel like living in a dystopia? Take a deep breath, get a strong coffee, and let uschallenge your ideas of where reality ends, and sci-fi begins...
Keywords: 300; Sci-fi; Information law; Artificial intelligence; Robotics; Algorithmic governance